Pemikiran Hadis Musthafa Al-Siba’i dan Muhammad Fuad Abdul Baqi: Analisis Komparatif terhadap Paradigma Studi Hadis Kontemporer - Sulaiman Hasyim, Muhammad; Ilyas, Muhammad (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study examines the hadith thought of two contemporary scholars, Musthafa al-Siba’i and Muhammad Fuad Abdul Baqi, along with their contributions to the development of modern hadith studies. The research uses a library research method by analyzing relevant primary and secondary sources. The findings reveal that Musthafa al-Siba’i refutes the notion of hadith forgery during the lifetime of the Prophet Muhammad and reaffirms the authenticity of the Sunnah through a historical and rational approach. Meanwhile, Muhammad Fuad Abdul Baqi made a major contribution to the field of takhrīj al-hadith through his works such as Al-Mu‘jam al-Mufahras li Alfādz al-Hadīth al-Nabawiy and Miftāh Kunūz al-Sunnah. Both figures play significant roles in revitalizing contemporary hadith studies with different yet complementary methodological orientations.